Fluid Mechanics for Chemical Engineering. - Mory, Mathieu (ISTE., 2013)
The book aims at providing to master and PhD students the basic knowledge in fluid mechanics for chemical engineers. Applications to mixing and reaction and to mechanical separation processes are addressed. The first part of the book presents the principles of fluid mechanics used by chemical engineers, with a focus on global theorems for describing the behavior of hydraulic systems. The second part deals with turbulence and its application for stirring, mixing and chemical reaction. The third part addresses mechanical separation processes by considering the dynamics of particles in a fl.